IMOGEN: an intermediate complexity model to evaluate terrestrial impacts of a changing climate - C. Huntingford; B. B. B. Booth; S. Sitch; N. Gedney; J. A. Lowe; S. K. Liddicoat; L. M. Mercado; M. J. Best; G. P. Weedon; R. A. Fisher; M. R. Lomas; P. Good; et al. (Geoscientific Model Development, 2010)
We present a computationally efficient modelling system, IMOGEN, designed to undertake global and regional assessment of climate change impacts on the physical and biogeochemical behaviour of the land surface. A pattern-scaling approach to climate change drives a gridded land surface and vegetation model MOSES/TRIFFID. The structure allows extrapolation of General Circulation Model (GCM) simulations to different future pathways of greenhouse gases, including rapid first-order assessments of how the land surface and associated biogeochemical cycles might change. Evaluation of how new terrestrial process understanding influences such predictions can also be made with relative ease.